Tracing Public Sentiments and Policy Changes Toward Canadian International Students Using LLM - Wang, Ya Xuan; Zha, Qiang (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
Recent Canadian higher education policies, such as the federal international student cap, reflect a growing nationalist-populist orientation. To understand how such policy directions emerge and gain traction, our study moves upstream from policy content to public discourse. We conduct a thematic analysis of social media posts (on Twitter/X) using a large language model (ChatGPT-5), comparing pre-pandemic (2015–2020) and post-pandemic (2020–2025) discourse. Our findings reveal a post-pandemic surge in negative sentiments, increasingly framing international students as competitors for housing, jobs, and public resources. We demonstrate that public discourse not only reflects individual perceptions but also drives national agenda-setting and gives momentum to restrictive policy measures within Canadian international higher education. Consequently, it is important for higher education leaders and policy makers to account for the policy implications of discursive scapegoating and to consider the role of social integration in sustaining internationalization efforts.